Relationship between Level of Parentâs Income and Nutritional Status of Under-Five Years Old Children in Punggawan Village, Banjarsari Districts, Surakarta. - MB, Reyhana; Suhanantyo, .; Widyaningsih, Vitri (Nexus Kedokteran Komunitas, 2015)
Background: Prevalence of malnutrition increase in past few years. Sixty six million under-five years old children around the world died in 2012 and 45% of them died due to malnutrition. The prevalence of under-five years old children who has suffered undernutrition is still increasing over 2007-2013. Undernutrition can be caused by imbalance of the intake, economical crisis, parentsâ lack of knowledge, parentsâ economical status (occupation and income), lack of healthcare services,Â  and infection among children that caused by viruses and bacteries. This study is aimed to measure the relationship between level of parentsâ income and nutritional status of under-five years old children in Punggawan Village, Banjarsari Districts, Surakarta. Methods: A cross sectional, observational study was conducted. This study was located in Punggawan Village, Banjarsari Districts, Surakarta from March 2014 until January 2015. The data was collected from October until November 2014 time period using questionaire and direct measurement of childrenâs weight and height. Sample of this study were under-five years old children in Punggawan Village, Banjarsari Districts, Surakarta. Their nutritional status were defined by several anthropometry indices such as weight for age, height for age, weight for height, and Body Mass Index for age. The parentsâ income was defined by their total income in rupiah (Rp). Data was analyzed by logistic regression doubling amount and Chi Square. Results: The result of bivariate logistic regression showed value of OR = 1.00 for correlation between level of parentâs income and indices of weight for age, height for age, weight for height, and Body Mass Index for age. This result showed that nutritional status was not associated with level of parentâs income. Conclusion: There is no relation between level of parentâs income and nutritional status of under-five years old children in Punggawan Village, Banjarsari Districts, Surakarta. Keywords: Parentâs income, nutritional status, parentâs education, occupationÂ